Unveiling the molecular mechanisms of γ-polyglutamic acid-mediated drought tolerance in cotton through transcriptomic and physiological analyses - Ziyu Wang; Xin Zhang; Yunhao Liusui; Wanwan Fu; Aixia Han; Dongmei Zhao; Jisheng Yue; Yongfeng Tu; Jingbo Zhang; Yanjun Guo (BMC Plant Biology)
Abstract Background Drought severely impacts the growth of cotton, and the application of plant biostimulants offers an effective approach to enhancing crop drought tolerance. γ-Poly-glutamic acid (γ-PGA) is a novel and environmentally friendly biostimulant, but its functions and mechanisms in responding to drought stress in cotton are still unclear. Results This study aims to elucidate the role of the plant biostimulant γ-PGA in the response of cotton to drought stress. Cotton seedlings treated with exogenous γ-PGA and a control group were subjected to drought conditions, and phenotypic observations along with measurements of relevant physiological indicators were conducted. The results showed that the activities of superoxide dismutase (SOD) and peroxidase (POD), as well as the proline (PRO) content in the leaves of γ-PGA-treated cotton, were higher than those in the control group, while malondialdehyde (MDA) content was lower. This indicates that exogenous application of γ-PGA can effectively enhance cotton’s tolerance to drought stress. Subsequently, transcriptome sequencing was performed on the leaves of cotton plants under drought stress in both the γ-PGA-treated and control groups. The results revealed that γ-PGA treatment led to the upregulation of 1,658 genes and the downregulation of 589 genes. Among these differentially expressed genes (DEGs), 233 were transcription factors, suggesting that γ-PGA participates in the cotton drought stress response by regulating the expression of numerous transcription factors. KEGG analysis showed that DEGs were primarily enriched in plant hormone signaling pathways (a total of 103 DEGs). Further analysis revealed that γ-PGA promotes the expression of genes related to ethylene (ETH), Brassinosteroids (BR) and abscisic acid (ABA) hormone signal transduction, indicating that it can enhance cotton’s tolerance to drought stress by regulating the signal transduction of these hormones. Conclusions This study elucidates the effects of exogenous γ-PGA on drought resistance in cotton, as well as the molecular mechanisms underlying this resistance. The findings provide a theoretical foundation for the future application of γ-PGA to enhance drought tolerance in cotton.